Analisis Kualitas Pelayanan pada Coworking Space di East Java Super Corridor (EJSC) Badan Koordinasi Wilayah Pemerintahan dan Pembangunan (BAKORWIL) II Bojonegoro - Tatha Pratamawati; Meirinawati Meirinawati (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
The East Java Provincial Government established the East Java Super Corridor (EJSC) in five regions, including Bojonegoro Regency, to provide coworking spaces for the public. EJSC Bakorwil Bojonegoro is the only coworking space in the area, making it essential to offer high-quality services. This study aims to describe the service quality of the coworking space at EJSC Bakorwil Bojonegoro using a descriptive qualitative method. This research focuses on the five service quality indicators proposed by Kotler and Keller (2016): reliability, responsiveness, assurance, empathy, and tangibles. Data were collected through interviews, observations, documentation, and literature studies, with data analysis involving collection, reduction, presentation, and conclusion drawing. The findings indicate that the service quality of the coworking space at EJSC Bakorwil Bojonegoro is generally satisfactory. Reliability is reflected in the provision of free facilities that support user productivity. However, responsiveness still faces challenges in terms of timely responses to complaints and the flexibility of operating hours. Assurance has been established through effective communication, although staff professionalism needs improvement. Empathy is demonstrated through warm and responsive interactions between management and users. Tangibles indicate that the available facilities are adequate, but some shortcomings remain, such as limited parking space and suboptimal workspace arrangement.